The Relationship Between The Use Of Media and The Learning Activities of Training Participants at Uptd BLK Padang Pariaman - Vikriani, Vadila; Natsir, MHD (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the active learning of training participants in the learning process at UPTD BLK Padang Pariaman, which was thought to be because the instructor used learning media that was less than optimal. This research aims to see a description of the use of media used by instructors in the learning process. The learning activity of trainees in the learning process and the relationship between the use of media and the learning activity of trainees at UPTD BLK Padang Pariaman. This type of research uses a correlational quantitative approach. The population in this study was all training participants at UPTD BLK Padang Pariaman, totaling 32 people. Meanwhile, samples were taken using the cluster random sampling technique as much as 75% of the population of 32 people so that the sample taken was 24 people. Data collection techniques use a questionnaire which will be distributed via Google Form. Meanwhile, the data analysis technique uses a percentage formula and to look for relationships using the rank order formula. The results of this research indicate that instructors have not used media optimally in the learning process so that the trainees' active learning in the learning process is low. There is a significant relationship between media use and the active learning of training participants at UPTD BLK Padang Pariaman.Keywords: use of media, learning activity